Zebrafish Ism1 is a novel antiviral factor that positively regulates antiviral immune responses. (December 2021) - Li, Congjun; Zhong, Shenjie; Ni, Shousheng; Liu, Zhenhui; Zhang, Shicui; Ji, Guangdong
Abstract: Isthmin1 (Ism1), first identified as a secreted protein in Xenopus embryos in 2002, has been shown to perform multiple biological functions, but little is known currently regarding its role in immunity. Here we show that the expression of ism1 is inducible by challenge with Grass carp reovirus (GCRV) in zebrafish, suggesting involvement of Ism1 in antiviral response. We then demonstrate that recombinant Ism1 (rIsm1) reduces the cytopathic effect in the cells infected by GCRV, promotes the expression of type I IFN gene and IFN-inducible antiviral protein Mxa gene, and reduces the virus quantity in virus-infected cells and host. We also show that rIsm1 promotes the expression of tbk1, irf3 and i rf7, suggesting it promotes the expression of type I IFN gene and Mxa gene via induction of Tbk1–Irf3–Ifn pathway. These data together indicate that Ism1 is a new immune-relevant factor functioning in antiviral immune response, and provides a target for controlling viral infection. Highlights: Expression of Isthmin1 (Ism1) gene was inducible by challenge with Grass carp reovirus (GCRV). Recombinant Isth1 (rIsm1) reduced cytopathic effect in cells infected by GCRV. rIsm1 reduced virus quantity in virus-infected cells and host. rIsm1 promoted expression of both type I IFN and Mxa genes via induction of Tbk1–Irf3–Ifn pathway.